An overexpression screen of Toxoplasma gondii Rab-GTPases reveals distinct transport routes to the micronemes - Kremer, K; Kamin, D; Rittweger, E; Wilkes, J; Flammer, H; Mahler, S; Heng, J; Tonkin, C; Langsley, G; Hell, S; Carruthers, V; Ferguson, D; et al. (Public Library of Science, 2013)
The basic organisation of the endomembrane system is conserved in all eukaryotes and comparative genome analyses provides compelling evidence that the endomembrane system of the last common eukaryotic ancestor (LCEA) is complex with many genes required for regulated traffic being present. Although apicomplexan parasites, causative agents of severe human and animal diseases, appear to have only a basic set of trafficking factors such as Rab-GTPases, they evolved unique secretory organelles (micronemes, rhoptries and dense granules) that are sequentially secreted during invasion of the host cell. In order to define the secretory pathway of apicomplexans, we performed an overexpression screen of Rabs in Toxoplasma gondii and identified Rab5A and Rab5C as important regulators of traffic to micronemes and rhoptries. Intriguingly, we found that not all microneme proteins traffic depends on functional Rab5A and Rab5C, indicating the existence of redundant microneme targeting pathways. Using two-colour super-resolution stimulated emission depletion (STED) we verified distinct localisations of independent microneme proteins and demonstrate that micronemal organelles are organised in distinct subsets or subcompartments. Our results suggest that apicomplexan parasites modify classical regulators of the endocytic system to carryout essential parasite-specific roles in the biogenesis of their unique secretory organelles.